2010
DOI: 10.1007/s11164-010-0161-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of N,N-dihexyloctanamide with nitrate and dodecane radicals: a pulse radiolysis study

Abstract: Recently, completely incinerable N,N-dihexyloctanamide (DHOA) has been identified as a promising alternative to tri-n-butyl phosphate for the reprocessing of spent nuclear fuels. The present work deals with the pulsed radiolytic investigation on the reactions of DHOA with the radicals produced in the radiolysis of nitric acid and dodecane medium. The rate constants of the reactions of DHOA with solvated electron, nitrate radical and dodecane radicals have been measured and the transients have been characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…radicals. 35 The authors evidenced the formation of the H-atom adduct C 7 H 15 C ? (OH)N(C 6 H 13 ) 2 and of the ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…radicals. 35 The authors evidenced the formation of the H-atom adduct C 7 H 15 C ? (OH)N(C 6 H 13 ) 2 and of the ?…”
Section: Discussionmentioning
confidence: 99%
“…N(C 6 H 13 ) 2 . 35 Hayon et al have studied the reactivity of HO ? radicals with amides in aqueous solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The tetradentate binding pocket made up by the nitrogen donor groups of CyMe 4 BTBP, should not be occupied [32]. In the literature, radiolysis of nitric acid is well described and especially radical scavenging by HNO 3 , NO 3or H + seems to be likely [33][34][35][36][37][38][39][40]. The individual infl uences of HNO 3 , NO 3or H + will therefore be investigated and further detailed investigations of the radiolysis mechanism are planned (e.g.…”
Section: Hplc-ms Analysismentioning
confidence: 99%
“…28,29 A pulse radiolysis method is ideal for the selective generation of radicals of interest under appropriate experimental conditions as the rate constants of a variety of reactions are well documented in the literature. [30][31][32][33][34] Precise knowledge about the yield of radicals makes the evaluation of kinetics easier and thereby rate constants as well as the extinction coefficients of the transients can be determined with good accuracy. It is reported that pulse radiolysis of malonamides has been carried out for the identification of the possible site of OH attack on N-methyl amides which was helpful for the study of radical formation in peptides and proteins.…”
Section: Introductionmentioning
confidence: 99%